Determinations of nutrients and metals content in composted liquid waste - Nordin, Muhammad Fadzli Shafiq; Abdullah, Shakila; Khamidun, Mohd Hairul (Penerbit UTHM, 2020)
High amount of food waste produced has been an issue for the municipal solid waste management system in Malaysia especially when there is no more landfill to cover for all the wastes. Composting is one of the solutions to decrease the amount of waste discharged especially for food wastes. This study is conducted to evaluate the nutrients content (NH3-N, PO43-, Mg2+, Ca2+, Na+, and K+) and metals (Cu, Pb, Ni, Cd, Cr, As). This includes the physicochemical parameters such as pH, colour, temperature, total suspended solid (TSS) and also radionuclide uranium. Heavy metals were detected using Inductively Coupled Plasma Mass Spectrometry (ICP-MS) and nutrients were determined using Atomic Absorption Spectrometer (AAS) and DR6000 Spectrophotometer (HACH). The result shows that most of the characteristics were in compliance with the standard discharge limit by Department of Environment (DOE). The high concentrations of nutrients can be potential for making it into organic fertilizer.